Social Behavior of Students from Families with Authoritarian Parenting Patterns (Strict Parents) in Makassar City - Rimaisya, A. Adissa Lutfiah; Sakaria, Sakaria; Syam, Ridwan (Formosa Journal of Applied Sciences, 2024)
This research aims to explore the impact of authoritarian parenting, characterized by strict and controlling parental involvement, on students' social behavior. In using a qualitative approach with a case study strategy, this research selected ten informants through a purposive sampling technique. Data was collected through in-depth interviews and participant observation. The findings show that students who were raised in an authoritarian upbringing tend to show obedient and submissive behavior, but also be exclusive and careful in socializing with them. They lack self-confidence in social environments and tend to have limited openness towards parents. Even though they are obedient in worship, they often violate their parents' rules and even lie to them. The implication of this research is a deeper understanding of how parenting can influence the development of students' social behavior, as well as the potential impact in the long term.